An Unusual Occurrence of Multiple Dental Anomalies in a Single Nonsyndromic Patient: A Case Report - N. B. Nagaveni (Hindawi Limited, 2012)
Dental anomalies are the formative defects caused by genetic disturbances or environmental factors during tooth morphogenesis. Simultaneous occurrence of various multiple anomalies has been reported previously, particularly in cases of chromosomal abnormalities that often manifest with multisystem involvement. Very few cases of multiple anomalies have been documented in patients with no known generalized abnormalities. The present paper shows an unusual occurrence of a combination of dental anomalies like mandibular canine transmigration, taurodontism in permanent mandibular molars, congenital agenesis of 14 numbers of permanent teeth excluding third molars, canine impaction, primary molars with pyramidal roots, midline diastema and generalized microdontia in an apparently normal 13-year-old Indian girl.